Advanced materials and engineering applications : selected, peer reviewed papers from the 2012 SREE conference on advanced materials and engineering applications (AMEA 2012), May 5-6, 2012, Hong Kong - Zhang, Jiatao (Applied mechanics and materials ;, 2012)
These are the proceedings of the SREE Conference on Advanced Materials and Engineering Applications (AMEA 2012), held on the 5 and 6th May, 2012, in Hong Kong. These 55 selected papers cover topics such as: Materials Science; Metallic Materials; Biological Materials and Medical Materials; Chemical Materials; Electronic / Magnetic / Optical Materials; other Materials; Advanced Materials and Applications in Engineering. The conference provides opportunity for theoretical and technical exchanges regarding the advanced theories, methodologies, and techniques about all aspects of advanced materials and their engineering applications. The 53 papers selected for publication, from 190 presentations, cover material science; metal materials; biological and medical materials; electronic, magnetic, and optical materials; chemical materials; other materials; and advanced materials applications in engineering. Specific topics include predicting the static contact angle in circular capillary tubes, properties of injectable composite cements and their application in burst fracture of the spine, the surface modification of epoxy-ceramic coatings by plasma treatment, and analyzing low frequency noise induced by a spring floating slab.